DESIGN OF RAKA DRYER WITH ETC TECHNOLOGY (ELECTRICAL TEMPERATURE CONTROL) - Irfan Malik Hartanto; Agam Seftian Effendi; Choirul Hamzah; Aldiansyah Rusminanda; Irenta Teguh Wahyu Widodo (Journal of the Community Development in Asia (JCDA), 2018)
The purpose of this study is to provide solutions for problems in SMEs katul leaven, especially the problem of drying process that the process is still using the traditional way and the tool is still relatively simple so less hygienic. The method used is to utilize sunlight, exhaust fan, and Heat Exchanger technology that supply electric energy from solar panels and operate semi-automatically. The expected result is the increased productivity and efficiency of the production process so that the productivity of SMEs leaven can increase twice from 40 kg / day to 80 kg / day.